Giants & witches, and a dragon or two - Fenner, Phyllis Reid 1899- (Knopf, 1943)
Seventeen stories, including both folk tales and a few original stories, about various creatures of fantasy, including Baba Yaga, King Stork, Jack the Giant Killer, and The Terrible Olli.